The discourse organization of Filipino homilies and Indian homilies: An intercultural rhetoric approach - Alamis, Ma. Melvyn P. (Animo Repository, 2013)
The study examined the discourse structure of homily as a genre. It investigated homilies delivered by Filipino and Indian priests that represent varied types of Englishes in the Outer Circle. It described the organizational moves present in the two sets of homilies. The data which consisted of sixty orally delivered homilies transcribed into written forms were culled from six Filipino priests and six Indian priests from the different Roman Catholic parishes/churches in and around Manila. The homilies were delivered in English from 2008 to 2010. Findings showed that both Filipino and Indian homilies employed the three moves which are obligatory: Introduction, Body and Conclusion and the sub-move Explanation. Based on the results of the analysis of the different moves in the homilies, the three moves were not left to be figured out by the audience. This may show that the homilies of the Catholic clergy employ an audience/listener responsibility. No significant differences were found in the frequency of occurrence of these moves.